Ultratight crystal packing of a 10 kDa protein. (24th March 2013) - Trillo‐Muyo, Sergio; Jasilionis, Andrius; Domagalski, Marcin J.; Chruszcz, Maksymilian; Minor, Wladek; Kuisiene, Nomeda; Arolas, Joan L.; Solà, Maria; Gomis‐Rüth, F. Xavier
<x xml:space="preserve">Abstract</x> While small organic molecules generally crystallize forming tightly packed lattices with little solvent content, proteins form air‐sensitive high‐solvent‐content crystals. Here, the crystallization and full structure analysis of a novel recombinant 10 kDa protein corresponding to the C‐terminal domain of a putative U32 peptidase are reported. The orthorhombic crystal contained only 24.5% solvent and is therefore among the most tightly packed protein lattices ever reported.